Immunohistochemical expression profiles of MUC1 and MUC2 mucins in urothelial tumors of bladder - Ipek Isik Gonul; Asli Cakir; Sinan Sozen (Wolters Kluwer Medknow Publications, 2018)
Background: Mucins may show aberrant expression, localization, and/or glycosylation in multiple malignancies. However, information regarding expression of these mucins is mostly unknown in urothelial tumors. Aim: This study was conducted for examining the expressions of membrane associated and secreted mucin (MUC1) and a secreted gel-forming mucin (MUC2) in urothelial tumors of the urinary bladder. Subjects and Methods: Archival transurethral resection materials of 97 urothelial carcinoma cases were reexamined light microscopically and graded according to the 2004 WHO Classification. Pathological stage was given as pTa, pT1, and pT2. Demonstrative sections were recut for immunohistochemistry for MUC1 and MUC2. The results were statistically analyzed, and P < 0.05 was considered statistically significant. Results: The positivity for MUC1 and MUC2 was 89.7% and 44.3%, respectively. Independent from pathological stage of the tumor, MUC1 expression showed statistically significant correlation with tumor grade (P < 0.05). We did not find any correlation between pathological stage and MUC1 and MUC2 expression (P > 0.05). MUC1 staining pattern in papillary urothelial neoplasm of low malignant potential cases was more commonly apical and superficial (luminal cell layer only). Intermediate cells ± basal cells or isolated cells or islands of tumor cells with cytoplasmic and/or circumferential membrane positivity for MUC1 and MUC2 were more commonly observed in both low- and high-grade carcinomas. The difference between groups in terms of MUC1 and MUC2 staining was statistically significant (P < 0.05). Conclusions: The staining patterns of both mucins are different between urothelial papillary tumors and may be used to make a differentiation, especially for low-grade papillary urothelial lesions. This difference may also be important in the carcinomatous transformation of urothelial neoplastic and preneoplastic lesions.